2022
DOI: 10.1111/idh.12615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antiplaque and anti‐gingivitis effects of aloe vera mouthwash with chlorhexidine in fixed orthodontic patients—A randomized controlled trial

Abstract: Background In daily dental practice, plaque‐induced gingivitis is one of the most common periodontal diseases that is frequently encountered. Accumulation of microbial biofilms on surfaces of teeth and poor or inadequate oral hygiene is the chief predisposing factor for this condition. In such a state, antimicrobial mouthwash as an adjunct to mechanical plaque control helps in maintaining good oral hygiene. Among the many conditions, fixed orthodontic treatment is one of the conditions where plaque control bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The systematic review included a total of nine studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], as summarized in Table 1 . These studies were conducted in various countries, including Spain [ 21 , 23 ], the United States [ 22 ], India [ 24 , 27 ], Brazil [ 25 , 26 ], Egypt [ 28 ], and Iran [ 29 ], over a period spanning from 2014 to 2022. Each study employed a randomized clinical trial design, focusing on evaluating the therapeutic properties of natural products in orthodontic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic review included a total of nine studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], as summarized in Table 1 . These studies were conducted in various countries, including Spain [ 21 , 23 ], the United States [ 22 ], India [ 24 , 27 ], Brazil [ 25 , 26 ], Egypt [ 28 ], and Iran [ 29 ], over a period spanning from 2014 to 2022. Each study employed a randomized clinical trial design, focusing on evaluating the therapeutic properties of natural products in orthodontic treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The quality assessment of these studies revealed a mix of medium and high ratings. Specifically, five studies [ 21 , 24 , 25 , 26 , 28 ] were rated as medium quality, indicating satisfactory adherence to standard research methodologies but potentially possessing some limitations in study design or execution. In contrast, four studies [ 22 , 23 , 27 , 29 ] received high-quality ratings, suggesting a robust study design, comprehensive methodology, and reliable results that adhere closely to the highest standards of clinical research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using 0.12% chlorhexidine as a positive control was based on knowing that chlorhexidine is a goldstandard chemical substance with an antibacterial action against gram-positive and gram-negative bacteria [45]. In this study, treatment with 0.12% chlorhexidine reduced C. albicans, L. casei, and S. mutans log 10 CFU/mL amount according to the exposure.…”
Section: Discussionmentioning
confidence: 96%